“I teach it because it is the biggest threat to health”: Integrating sustainable healthcare into health professions education - Brand, Gabrielle; Collins, Jorja; Bedi, Gitanjali; Bonnamy, James; Barbour, Liza; Ilangakoon, Chanika; Wotherspoon, Rosie; Simmons, Margaret; Kim, Misol; Schwerdtle, Patricia (Medical teacher, 2021)
Steering planetary and human health towards a more sustainable future demands educated and prepared health professionals. This research aimed: to explore health professions educators’ sustainable ...
Online veröffentlicht: 12 Nov 2020
Gesehen am 02.05.2024